Pengaruh Kepemimpinan, Disiplin Kerja, Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Optik Di Kecamatan Cakranegara - RR Mauryta Angkasa Putri; Hj. Erviva Fariantin; Rosyia Wardani (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This research aims to examine the influence of leadership, work discipline and work environment on job satisfaction of optical employees in Cakranegara District. Data was collected via a Google Form questionnaire from 51 employees. The data analysis used is the t test (partial), and F test (simultaneous). The results of the t test analysis (partial), show (1) leadership has a negative and not significant effect with a calculated t value of -0.560 < t table 2.01174 and a significance level of 0.578 > 0.05, (2) work discipline has a positive but not significant effect on t value 1.439 < t table 2.01174 and a significance level of 0.456 > 0.05, (3) the work environment is proven to have a positive and significant effect on job satisfaction of optical employees with a t value of 5.628 > t table 2.01174 and a significance level of 1.259 < 0.05. The results of the F test analysis found that leadership, work discipline and the work environment simultaneously had a significant effect on optical employee job satisfaction with a calculated F value of 55.039 > F table 2.80 and a significance level of 0.000 < 0.05